HPV16/HPV58 viral load is non-linearly correlated with cervical lesions and can be used as a triage marker - Jie Zhou; Bingbing Ma; Jinjin Ji; Jianhong Liao; Hongyan Xu; Hongbo Hu (Infectious Agents and Cancer)
Abstract The significance of viral load from high-risk human papillomavirus (HR-HPV) in the detection of cervical lesions is still debated. This study aims to assess the correlation between the viral load of the most common high-risk genotypes (HPV16, HPV18, HPV52, HPV53, HPV58, and HPV68) and cervical lesions in South China, and to ascertain the role of specific HPV viral load types as potential diagnostic biomarkers for cervical lesions. The study included 1787 patients, with HPV types and viral load measured by fluorescent PCR method. The relationship between viral load and cervical lesions was analyzed through both linear and non-linear methods. Viral loads of HPV 16/18/52/58 are risk factors for the occurrence of cervical lesions, Notably, HPV16 and HPV58 respectively demonstrated a non-linear association with the emergence of CIN1 + and CIN2 + cervical lesions, indicating that HPV viral load may serve as a stratification marker for recognizing heightened risk of cervical lesions, thus enhancing risk stratification in cervical cancer screening.